Long-life and deeply rechargeable aqueous Zn anodes enabled by a multifunctional brightener-inspired interphase. Issue 6 (3rd May 2019) - Zhao, Zhiming; Zhao, Jingwen; Hu, Zhenglin; Li, Jiedong; Li, Jiajia; Zhang, Yaojian; Wang, Cheng; Cui, Guanglei
Abstract : A brightener-inspired polymer interphase enables highly reversible aqueous Zn anodes via suppressing side-reactions and manipulating the nucleation process. Abstract : Aqueous Zn anodes have been revisited for their intrinsic safety, low cost, and high volumetric capacity; however, deep-seated issues of dendrite growth and intricate side-reactions hindered their rejuvenation. Herein, a "brightener-inspired" polyamide coating layer which elevates the nucleation barrier and restricts Zn 2+ 2D diffusion is constructed to effectively regulate the aqueous Zn deposition behavior. Importantly, serving as a buffer layer that isolates active Zn from bulk electrolytes, this interphase also suppresses free water/O2 -induced corrosion and passivation. With this synergy effect, the polymer-modified Zn anode produces reversible, dendrite-free plating/stripping with a 60-fold enhancement in running lifetime (over 8000 hours) compared to the bare Zn, and even at an ultrahigh areal capacity of 10 mA h cm −2 (10 mA cm −2 for 1 h, 85% depth of discharge). This efficient rechargeability for Zn anodes enables a substantially stable full-cell paired with a MnO2 cathode. The strategy presented here is straightforward and scalable, representing a stark, but promising approach to solve the anode issues in advanced Zn batteries.